Calving Behavior at Rink Isbræ, West Greenland, from Time-Lapse Photos. Issue 2 (1st May 2016) - Medrzycka, Dorota; Benn, Douglas I.; Box, Jason E.; Copland, Luke; Balog, James
ABSTRACT: This study presents detailed observations of calving behavior variability from daily oblique photographs acquired over a five-year period (2007–2011) covering the terminus of Rink Isbræ, a major West Greenland outlet glacier. The evidence suggests that calving at Rink is characterized by two styles with distinct temporal and spatial footprints. The first style is characterized by frequent small magnitude events, which show clear seasonal variability with a marked increase in frequency immediately following ice mélange breakup and a peak in July. The second style is characterized by the sporadic detachment of kilometer-sized tabular icebergs with no clear seasonal signal. We suggest that two sets of mechanisms control calving variability at this location, namely (1) melt-driven processes enhancing submarine undercutting and (2) mechanically driven buoyant flexure. The presence of sea ice and/or ice mélange in the fjord presents an additional factor limiting calving in the winter.